2019
DOI: 10.1111/jcmm.14427
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human adipose derived stem cells into Leydig‐like cells with molecular compounds

Abstract: Leydig cells (LCs) are the primary source of testosterone in the testis, and testosterone deficiency caused by LC functional degeneration can lead to male reproductive dysfunction. LC replacement transplantation is a very promising approach for this disease therapy. Here, we report that human adipose derived stem cells (ADSCs) can be differentiated into Leydig‐like cells using a novel differentiation method based on molecular compounds. The isolated human ADSCs expressed positive CD29, CD44, CD59 and CD105, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The cell inoculation method used for the treatment of Leydig cell dysfunction‐related diseases is also controversial. Chen Yong et al induced human ADSCs to differentiate into Leydig‐like cells in vitro and inoculated them into rats with Leydig cell damage. Although the testosterone levels in these rats increased, this direct testicular transplantation technique required an invasive operation, which might aggravate testicular injury, and the cell survival rate after transplantation could not be guaranteed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell inoculation method used for the treatment of Leydig cell dysfunction‐related diseases is also controversial. Chen Yong et al induced human ADSCs to differentiate into Leydig‐like cells in vitro and inoculated them into rats with Leydig cell damage. Although the testosterone levels in these rats increased, this direct testicular transplantation technique required an invasive operation, which might aggravate testicular injury, and the cell survival rate after transplantation could not be guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have multilineage differentiation potential and greater potential for application than Leydig stem cells. Compared with other MSCs, adipose‐derived stem cells (ADSCs) have the advantages of easy acquisition, reduced immunogenicity and an enhanced differentiation capacity . Many preclinical studies have studied the roles of ADSCs in promoting chronic diabetic wound healing and skin regeneration as well as the regeneration of cartilage tissue and liver cells .…”
Section: Introductionmentioning
confidence: 99%
“…To add to this, an adequate human embryonic gonadal cell line is currently lacking. We and others have begun to address this issue using differentiation methods for pluripotent stem cells into several cell types of the embryonic gonad, that is, bipotential cells, early Sertoli cells, and immature LCs [Bucay et al, 2009;Buganim et al, 2012;Yang et al, 2015Yang et al, , 2017Sepponen et al, 2017;Rodriguez Gutierrez et al, 2018;Chen et al, 2019;Knarston et al, 2020]. We have observed the induction of DHH expression in 3D organoid cultures, thus providing a valuable future tool to investigate the role of key testicular genes such as DHH during human fetal testis development [Knarston et al, 2020].…”
Section: Outstanding Questionsmentioning
confidence: 95%
“…Three studies reported recently by the Guo's group showed that stem cells from 3 different human sources were all successfully transdifferentiated into Leydig-like cells by external inducing factors. 53 54 55 The source cells included iPSCs, multipotent adipose-derived stem cells (ADSCs), and umbilical cord mesenchymal stem cells (UMSCs). The differentiation strategies were conducted via multiphase induction protocols.…”
Section: Generation Of Testosterone-producing Leydig-like Cells ...mentioning
confidence: 99%
“…As discussed above, stem cells from various sources have been successfully transdifferentiated into testosterone-producing Leydig-like cells by exogenous factors. 53 54 55 Conversion of human fibroblasts into neuron-like cells without overexpression of TFs has also been performed using a combination of small molecules. 75 This strategy offers a simpler and safer alternative for transdifferentiating stem cells or reprogramming differentiated cells for disease modeling and regenerative medicine.…”
Section: Generation Of Testosterone-producing Leydig-like Cells ...mentioning
confidence: 99%